Inovasi Model dan Strategi Pembelajaran pada Mata Pelajaran Fiqih di MA Nizhamiyah Ploso Jombang - Ahmad Bahrul Musyaffak; Mohammad Saat Ibnu Waqfin (ISLAMIKA, 2023)
Updating learning models and strategies in education is very important to suit the digital era, this is one of the supporting and inhibiting factors to continue to spur new innovations in learning models and strategies. so it becomes an answer with time. in educational foundations. Learning models and strategies are often applied by teachers using monotonous learning models, especially in Islamic jurisprudence subjects. It is necessary for the teacher to know about new innovations in learning models and strategies so that students understand the problems of fiqh which are always increasing with the times. The refore this research aims to: 1) find out the innovation of learning models and their application to fiqh subjects at MA Nizhamiyah. 2) to find out the innovative learning strategies and their application to fiqh subjects at MA Nizhamiyah. 3) to find out the inhibiting factors in model innovation and learning strategies in fiqh subjects at MA Nizhamiyah. In this study, the researcher took the title "Innovation of learning models and strategies in fiqh subjects at MA Nizhamiyah Ploso". The method in this study uses descriptive qualitative research. Data collection techniques in this study using observation techniques, interviews and documentation. The types and sources of data used are primary and secondary data by analyzing data validity techniques. The results of this research are that the teachers at MA Nizhamiyah describe model innovations and learning strategies in fiqh subjects that can be used, various models and strategies as well as inhibiting factors. That Innovation Models and learning strategies can be created by updating some or all of the components of learning models and strategies by updating or replacing them by making models and strategies that are suitable for the school.